Hippocampal GFAP and MAP2 mRNA expressions of curry leaves extract treatment in 2VO rats of neurodegeneration - Babar, Z.M.; Azzubaidi, Marwan Saad; Sulaiman , Wan Azizi; Talib, Norlelawati A. (2014)

(untitled)
Background: Experimental neurodegeneration can be induced by two-vessel occlusion intervention (2VO). Nigella sativa (Linn.) seeds extract (NSSE) has recently shown to enhance memory and learning task performances in rats with 2VO. Prevention of neuroinflammation and/or of toxic free radical formation are possible mechanisms. The glial fibrillary acidic protein (GFAP) is a vital neuroinflammatory marker in neuroscience researches. GFAP was found to be up-regulated in 2VO rats indicating astrogliosis. Microtubule associated protein type II (MAP2) is an important marker for neuroprotection during and after ischemic brain injury or hypoxia. It was found to be down-regulated in 2VO rats. Objective: The current study aimed to compare the hippocampal MAP-2 and GFAP mRNA expressions of 2VO (untreated) male rats in the experimental neurodegeneration with other groups of rats treated with NSSE. Method: 18 adult male Sprague Dawley rats were randomly divided into 3 groups (n=6); Healthy Control (HC); 2VO- without treatment (2VO); 2VO+NSSE-treated (NSSE). The NSSE group was pre-treated (2ml, 50 mg/kg/day, orally) for 10 days prior to 2VO surgery and continued until all animals were sacrificed at the end of 10th postoperative week. Hippocampal samples were then collected; total RNA was extracted, purified and relatively quantified via reverse transcribed cDNA as per ∆∆Cq of RT-qPCR assay. Results: There was a significant 3 folds difference of GFAP mRNA expression in both HC and NSSE groups as compared to that of 2VO. However, GFAP mRNA expression difference was not significant (P=0.52) of for NSSE vs. HC. Hippocampal MAP2 mRNA expression of NSSE group appeared to be insignificantly different from the untreated 2VO group. Conclusion: Prolonged treatment with NSSE has the potential to prevent hypoperfusion-induced neuroinflammation within the hippocampus. This may be a potential mechanism for neuroprotection against mild cerebral ischemic injuries. However, NSSE was unable to prevent loss of neuronal plasticity.